2020
DOI: 10.1002/jmri.27273
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Fiber Coherence of Amygdala−Accumbens−Pallidum Pathway Is Associated With Disorganized Nigrostriatal−Nigropallidal Pathway in Parkinson's Disease

Abstract: Background: Motor disturbances in Parkinson's disease (PD) mainly result from the degeneration of classic motor pathways. Given that the specific limbic pathway participates in movements, it is reasonable to consider that limbic pathway have the pathologic potential of motor disturbance in PD. Purpose: To explore the white matter changes of limbic and motor pathways and their relations in PD patients. Study Type: Prospective. Population: 39 PD patients and 55 normal controls. Sequence: Sagittal 3D T 1-weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The loss of dopaminergic neurons in SN is considered to reduce the dopaminergic function of connections from the SN pars compacta to the corpus striatum, known as the nigrostriatal pathway, leading to the characteristic motor signs of PD [ 124 ]. Andica et al [ 125 ] and Guo et al [ 126 ] used NODDI to report decreased ICVF and ODI, respectively, in the nigrostriatal pathways of patients with PD compared to the controls. Interestingly, the changes in ICVF were only observed in the contralateral distal part of the nigrostriatal pathway, suggesting retrograde degeneration [ 125 ].…”
Section: Applications Of Advanced Diffusion Mri Techniques In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of dopaminergic neurons in SN is considered to reduce the dopaminergic function of connections from the SN pars compacta to the corpus striatum, known as the nigrostriatal pathway, leading to the characteristic motor signs of PD [ 124 ]. Andica et al [ 125 ] and Guo et al [ 126 ] used NODDI to report decreased ICVF and ODI, respectively, in the nigrostriatal pathways of patients with PD compared to the controls. Interestingly, the changes in ICVF were only observed in the contralateral distal part of the nigrostriatal pathway, suggesting retrograde degeneration [ 125 ].…”
Section: Applications Of Advanced Diffusion Mri Techniques In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Interestingly, the changes in ICVF were only observed in the contralateral distal part of the nigrostriatal pathway, suggesting retrograde degeneration [ 125 ]. Furthermore, Guo et al [ 126 ] reported decreased ODI, together with a trend of increasing FA in the contralateral amygdala-accumbens-pallidum pathway, which suggested hyperconnectivity related to pathological progression.…”
Section: Applications Of Advanced Diffusion Mri Techniques In Neurodegenerative Diseasesmentioning
confidence: 99%
“…4 In the current issue of the Journal of Magnetic Resonance Imaging, the article by Guo et al attempts to investigate the microstructural changes of limbic and motor pathways and their relations to reveal the potential pathological foundation regarding motor disruption in Parkinson's disease (PD) by using single-and two-shell diffusion MRI. 5 Probabilistic tractography was used to reconstruct the nigrostriatal, basal ganglia-motor cortex and amygdala-accumbens-pallidum pathways in a total of 94 participants (55 healthy controls [HC] and 39 PD patients). Diffusion tensor imaging (DTI) 6 metrics-fractional anisotropy (FA) and mean diffusivity (MD)-were calculated from single-shell diffusion images.…”
mentioning
confidence: 99%
“…Aberrant enhanced coherence of the limbic pathway (ODI) was also significantly positively correlated with the degeneration of the nigrostriatal pathway (MD), thus suggesting a relevant role of the limbic-motor interface in the pathophysiology of PD. 5 Although diffusion MRI and tractography have raised interest in the last decades, some limitations need to be considered. Indeed, these tools present strengths but also weaknesses and intrinsic technical shortcomings.…”
mentioning
confidence: 99%
See 1 more Smart Citation